Factors associated with goals and goal scoring opportunities in professional soccer - Wright, C.; Atkins, S.; Polman, R.; Jones, B.; Sargeson, L. (International Journal of Performance Analysis in Sport, 2011)
The aim of the present study was to investigate the factors associated with goals and goal scoring opportunities in soccer taking into consideration a broader range of performance indicators. The study was part exploratory but, based on the current literature, we also developed some a priori predictions. In particular, it was predicted that (a) most goals would be scored within the penalty area (> 70%); (b) approximately 30% of goals would be scored from set plays and (c) the majority (> 70%) of goals would be scored from a relatively short (< 4) passing interchange. Data was collected from 1788 attempts and 169 goals for an English FA Premier League season. The Web-soft snapper performance analysis tool was used to time code when attempts on goal were made and the associated behaviours relating to the attempt on goal. All a priori predictions were supported. The binary logistic regression identified 3 covariates which had a significant (P < 0.05) impact on goals scored. This included position of attempt; goal keepers' positions and type of shoot. Transitions in play accounted for 63% of all goals scored and well over half of all attempts on goal. Although similarities were evident between this and previous literature, this investigation also highlighted the importance of other key variables associated with goals and goal scoring opportunities. The high contribution of factors associated with transitions in play helped to uncover the importance of tracking goals and goal scoring opportunities back to their point of origin.